Nêmesis: o papel da vingança no Direito Penal - Figueiredo, Maria Patricia Vanzolini (2014)
The included study is intended to investigate the functions and purposes of the penalty from a legal and ethnographic perspective, with support , especially in the work of René Girard. The work begins with a conceptual distinction between function and purpose that will determine the plans in place that will develop the arguments used. Passes to the critical analysis of preventive theories, aiming to demystify the varied discourses based on prevention. Next, we analyze two possible alternatives to preventive theories, namely, the retributive theories and the Ferrajoli theory, also pointing out its flaws and inconsistencies. From that deconstruction can spend to build a grounded in archaeological research on the origins of violence and profiles, as well as strategies designed to manage it proposed. In this step, it first explores the genealogy of violence and the outbreak of mimetic crisis. Then preventive methods (rigidity of customs, war, sacrifice) and curative (private revenge and judicial pen) management of violence, culminating with the statement that the function of the sentence coincides with the completion of vengeance. In the last chapter, it is stated, connected with the function, the purpose of punishment, which is the realization of revenge avoiding the outbreak of mimetic crisis and is outlined in general terms how this purpose can be achieved